ANALISIS PAYBACK PERIOD MODAL PENYERTAAN BUMDES SENDANG AGUNG MAKMUR PADA UNIT USAHA WARUNG LAMONGAN : Payback Period, BUMDes, Participation Capital, WarLA - Surur, Miftachus (Fakultas Ekonomi Universitas Gresik, 2020)
In the management of funds which primarily sourced from participating capital, BUMDes must use various financial management analyzes so funds can be managed clearly and can achieve the objectives of the BUMDes itself. One of the analyzes can be used to manage these finances is payback period analysis, payback period analysis makes the business plan that is carried out more measurable and has a clear direction. When the analysis is in accordance with the calculations, BUMDes can easily determine the next type of business in the effort to develop the business unit of the BUMDes itself. This research a case study, with primary and secondary data sources obtained through interviews, observation and documentation which are then managed by the triangulation method. From a business point of view payback period analysis the WarLA BUMDes Sendangagung business unit takes a time 15.3 years to return capital through net income from the business unit alone, but if it calculated using the overall net income of Sendangagung BUMDes from various units existing business, it will take faster, namely 1 year or 12 months to return the capital, assuming the BUMDes net income from August to December 2020 is at least Rp. 7,703,000, -. However, when viewed from the point of view of benefits, the existence of WarLA is quite beneficial in boosting the community's enthusiasm for entrepreneurship.